Peran Program Puspaga Dalam Upaya Pencegahan Kekerasan Terhadap Anak di Wilayah Kelurahan Made, Kecamatan Sambikerep, Kota Surabaya, Jawa Timur Indonesia - Dharma Wicaksana Putra; Radjikan Radjikan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Cases of violence against children have recently occurred so frequently that they have become a topic every day and are often underestimated in their environment. Violence against children carried out by irresponsible people can cause physical, psychological misery or suffering, depression and anxiety. Children are a generation of youth who are the nation's successors and should be protected by parents, family, society, local government and the state. Child protection is a form of activity to guarantee and protect children and the child's right to have a meaningful life, to get health services for themselves and children must also get a decent life in terms of shelter, clothing, nutritious food as food for the child's growth and development and care. medical services to a high standard if the child is sick or has an accident. Protection of children with character is to fulfill the needs and rights that they should get in order for them to be able to live, grow and thrive. In reality, children in Indonesia are very worrying because there are many cases such as bullying, sexual violence against children, and commercial sexual exploitation. In the Child Protection Law, violations of the protection (protection) of children's rights are not only violations of human rights, they are also a huge obstacle to the survival and growth of children. The role of PUSPAGA (Family Learning Center) is in carrying out prevention so that similar cases do not occur again in the community by conducting outreach to the community as a prevention effort.